Large spin-dependent tunneling magnetoresistance in Fe3O4/PET heterostructures developed at room temperature: A promising candidate for flexible and wearable spintronics - Mohammad Shahnawaze, Ansari; Mohd Hafiz Dzarfan, Othman; Mohammad Omaish, Ansari; Sana, Ansari; Norazlianie, Sazali (Elsevier, 2021)
Half-metallic nanocrystalline magnetite (Fe3O4) thin films, with different thicknesses were developed on polyethylene-terephthalate (PET) substrates, by reactive sputtering at room temperature. Fe3O4 film (200-nm thick)/PET heterostructures possess superior electrical and magnetic characteristics, with a Verwey transition temperature (Tv) of ~122 K and a saturation magnetization (Ms) ~ 361 emu/cm3. Furthermore, the antiferromagnetic (AFM)-coupled antiphase boundaries (APBs) controlled the transport properties of the Fe3O4 thin films, due to the tunneling of spin-polarized electrons through the films. Very-high magnetoresistance (MR) value (−8.9%) were observed for HFilm plane, constructed from Fe3O4 (200-nm thick)/PET when H values were below 60 kOe at 300 K. In addition, flexibility tests, to examine resistivity, M-H and MR, were performed using with 90° and 45° bent angles and cyclability experiments were implemented to validate the reproducibility of these characteristics. These outcomes demonstrated that Fe3O4/PET heterostructures may represent a promising candidate for flexible/wearable spintronics.